Outcomes of Extravesical Versus Intravesical Ureteral Reimplantation - Leah P. McMann; Byron D. Joyner (The Scientific World Journal)
Purpose: The purpose of our study was to examine outcomes and compare length of stay after extravesical and intravesical ureteral reimplantation at our institution. Materials and Methods: Retrospective review was performed of 30 patients (55 ureters) with vesicoureteral reflux who underwent either the Cohen (intravesical) cross-trigonal procedure or the extravesical (detrusorrhaphy) approach. Each patient had documented follow-up consisting of a postoperative renal ultrasound and/or a voiding cystourethrogram (VCUG). Inclusion criteria was the presence of primary vesicoureteral reflux. Exclusion criteria were patients who had undergone a previous repair and patients in whom results of neither the renal ultrasound nor the VCUG were available. Results: There were no significant cases of obstruction or wound infection with either approach. Two patients who underwent the extravesical approach had persistent reflux on VCUG three months postoperatively, but both resolved by fifteen months. Average length of stay was only 3.00 ± 1.33 days for the extravesical approach, compared to 5.36 ± 1.75 days for the intravesical approach ( P = .0003 ). Conclusions: Given that by fifteen months success rates were the same with either approach, the extravesical approach is comparable to the intravesical technique and is a viable option in terms of outcome and economics given the shorter length of hospital stay.